(Un)Seeing Goa’s Bom Jesus in Vishvesh Kandolkar’s This is Not the Basilica! - R. Benedito Ferrão (Imaginations: Journal of Cross-Cultural Media Studies, 2023)
This article examines the interrogation of visual history associated with Goan church architectural legacies offered by Vishvesh Kandolkar’s installation series, This is Not the Basilica! (2021). The artist’s subject is the 16th-century Basilica of Bom Jesus, which was built in locally domesticated Baroque style during Goa’s Portuguese colonial era and which houses the remains of the Spanish saint, Francis Xavier. Kandolkar’s work makes viewers intimate with the Basilica’s history, I contend, so as to posit the need for conservation efforts that will save the deteriorating church while also revealing its unseen aesthetic past as a symbol of still-unfolding Goan identity.